Migrations of Concepts - Diana, Rosario (Brepols, 2023)
Migrations of Concepts brings together the results of an experimental research on the migration of philosophical concepts into the languages of the arts. The monograph explores the intersection of philosophy, literature and art and presents a theoretical-performative investigation on the transposition of philosophical contents into theatrical and musical performance. Starting with Giambattista Vico and Samuel Beckett, a first part elaborates the paradigm of the ‘Disbelonging’ of the I – which is the condition of the I who realizes that it is both its own and foreign at the same time –, shows how this is transposed into the language of sounds, and reflects on the significance of public performance of a philosophical work. The second and third parts further explore the transposition of philosophical thought into art by presenting the theatrical performances written and directed by the author. More specifically, the book contains the text of two theatre readings on Vico and Gorgia, and the libretto of two melologues dedicated to Hegel and the Prince of Sansevero, with the corresponding scores of music composed by Rosalba Quindici. By exploring the boundaries of adaptation studies this monograph radically proposes a new and innovative way to study and communicate philosophical concepts.